2022
DOI: 10.5114/pjr.2022.116192
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of severity of COVID-19 pneumonia on computed tomography of the chest in vaccinated and non-vaccinated individuals: an observational study

Abstract: Purpose Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel virus causing an infectious disease, coronavirus disease 2019 (COVID-19). Computed tomography (CT) of the chest plays a significant role in the diagnosis and prognosis of COVID-19 using computed tomography severity scoring (CT-SS). Numerous vaccines are being made available in the world to lessen the effect of the COVID-19 pandemic. The purpose of the current study is to compare the severity of COVID-19 pneumonia using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…COVID-19 was mild in the vaccinated group compared to unvaccinated group. Covishield vaccine administration reduces the severity of COVID-19 pneumonia as compared to the nonvaccinated group, with a marked reduction in mortality (5) . Prior COVID-19 was associated with protection against any recurrent COVID-19 infection, against hospitalization and also against COVID-19 not requiring hospitalization (8) .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…COVID-19 was mild in the vaccinated group compared to unvaccinated group. Covishield vaccine administration reduces the severity of COVID-19 pneumonia as compared to the nonvaccinated group, with a marked reduction in mortality (5) . Prior COVID-19 was associated with protection against any recurrent COVID-19 infection, against hospitalization and also against COVID-19 not requiring hospitalization (8) .…”
Section: Discussionmentioning
confidence: 95%
“…After a mean interval of 5 days CT-chest has sensitivity of 97% in the diagnosis of COVID-19 pneumonia. CT-chest findings that are classically seen in COVID-19 pneumonia include ground glass opacities with bilateral, peripheral, and basal predominance with or without consolidation (5) . It was also noted that blood group of individual plays a role in immunopathogenesis of COVID 19 infection, individuals with blood group ' A' were higher susceptibility to infection and propensity to severe disease compared to group 'O' individuals less likely (6) .…”
Section: Intorudctionmentioning
confidence: 99%
“…In the study of Sagiraju et al, it was shown that full dose vaccination reduces the risk of severe disease and mortality, regardless of the vaccine type[ 15 ]. In the study of Mahajan et al [ 16 ], where they evaluated vaccinated and unvaccinated patients with a positive SARS-CoV-2 PCR test, they found that the CT-SS of vaccinated people was mild-moderate, while unvaccinated individuals were moderate-severe. Again, in the studies conducted by Russo et al [ 4 ], Ravindra et al [ 5 ], Fatima et al [ 6 ], and Yavuz et al [ 17 ], when the CT SS of vaccinated and unvaccinated patients were compared, it was shown that vaccinated patients had milder pulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Lee et al reported results on CT findings limited to a small population of partially (n = 64) or completely vaccinated (n = 22) patients [21]. Furthermore, these studies [19][20][21][22] showed contrasting results regarding the extent of COVID-19 lung involvement depending on the different vaccination statuses.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the extent of pneumonia at the initial CT exam has major prognostic value [18]. Some authors recently described differences in pneumonia rates and CT findings between patients with complete or incomplete vaccination cycle [19][20][21][22]. However, these studies showed evidence limited to a population vaccinated with inactivated virus vaccine BBV152 viz.…”
Section: Introductionmentioning
confidence: 99%